Agnikarma Intervention for Avabahuka (Frozen Shoulder): A Systematic Review: Life Sciences-Ayurveda - Kumar, Mahesh; R.K, Shinde; Reena, Jaiswal (International Journal of Life Science and Pharma Research, 2022)
The Avabahuka is a common Vatavikar (disorder due to Vatadosha) described in ancient Ayurvedic literature like the Charak Samhita, Sushruta Samhita, Ashtanga Hridaya, etc. The Avabahuka disease affects Ansha sandhi (shoulder joint) and its clinical features are closer to the frozen shoulder (FS) of a modern musculoskeletal disorder, which is a common shoulder disorder. Synovial inflammation occurs in FS, followed by capsular fibrosis. The shoulder joint becomes gradually painful and stiff with a reduction in range of motion. Numerous treatment modalities are available for the treatment of Avabahuka as well as frozen shoulder. Traditional and surgical approaches are in practice, but each one has its limitations. Agnikarma, the intentional therapeutic heat burn therapy is an Ayurvedic treatment modality practice for the treatment of Avabahuka. The aim and objective is to prepare a comprehensive literature review of the subject. The study design is systematic literature review. The related article was searched in Ayurvedic text books and on the web. The matters were also searched on google scholar, PubMed, chochrane library, scopus library etc which are available. The thorough study of searched available matters, drafted, analysed and then draw a conclusion. The review suggests that the Agni karma intervention is an effective treatment modality in Avabahuka disease. This review is appraisal of available matters and is very helpful for researchers, clinicians, and pharmaceuticals companies who are involved or plan the work in particular subjects. Summarily this systematic review shows that the Agnikarma is helpful for the management of Avabahuka by virtue of heat and its vata and kaphashaamak nature. Agnikarma improves rasarakta circulation by its ushna (hotness), sukshma(penetration) and ashukari(fast acting) quality. Some more research studies are desired for experimental and clinical validation.